Can the morphological attributes of greater palatine foramen have implications in maxillary nerve block? An analytical study using anatomical planes - Ravi Kant Narayan; Sanjib Kumar Ghosh (Elsevier, 2021)
Introduction: Most popular approach for maxillary nerve block is via greater palatine canal (GPC) which is often difficult to access due to anatomical variations of its entry point the greater palatine foramen (GPF) thus resulting in failure of nerve block. It was hypothesized that exploring morphology of GPF with a modified approach may be useful towards its localization in an accurate manner. Materials & methods: The study was conducted on 35 dry adult human skulls with help of anatomical planes and quadrants on surface of hard palate on both sides of mid-sagittal plane (MSP). Results: It was observed that GPF was located predominantly in Md2 and M2 quadrants with an incidence of 88.83% and 88.84% on the left and right side of MSP respectively (when third maxillary molar is present) and in 100% cases on both sides of MSP (when third molar is absent). MSP was identified as preferred plane for GPC approach because of its proximity to upper incisors. Two rectangular areas were identified around point of intersection (Px) between P2 and P3 anatomical planes (5 mm anterior to Px, 2 mm posterior to Px and 2 mm on either side of Px) and posterior to point of intersection (Py) between P2 and P4 anatomical planes (5 mm posterior to Py and 2 mm on either side of Py) with high incidence of GPF when third molar is present or absent respectively. Conclusion: The observations from this study may reduce risk of error in localizing GPF during maxillary nerve block.